Hypomagnesemia in Pre-Renal Acute Kidney Injury Patients with Non-Recovery of the Renal Functions - Hafeez, Zahid; Hafeez, Rana Shahid; Ahmad, Fawad; Anwar, Wasif; Matee, Sumeera (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the hypomagnesaemia frequency in pre-renal acute kidney injury (AKI) patients with non-recovery of renal functions.Study Design: Cross-sectional study.Place and Duration of Study: Al-Noor Specialist Hospital Holy Makah, Saudi Arabia, from Jul 2014 to Jan 2015.Methodology: A total of 150 acute kidney injury patients qualifying the inclusion/exclusion criteria were enrolled in this study. Serum magnesium (Mg) levels were measured for all the patients. Serum magnesium level